The Role of Quality Assessment for Development of Sustainable Bus Service in Mid-sized Cities of India: A Case Study of Patna. (2017) - Sinha, Sanjeev; Sadhukhan, Shubhajit; Priye, Shiv
Abstract: Public transport in urban areas has been observed to have contributed significantly to the reduction of traffic congestion and pollution, providing alternate means of sustainable transport mode and in a general improvement in 'quality of life' of city dwellers. In developing countries like India, rapid urbanization has led to increased travel demand, an increase in a number of the personalized vehicles; however, lack of commensurate comprehensive transportation planning in urban areas has put tremendous pressure on the existing inadequate and out of date transport infrastructure. In order to overcome such alarming situation, improved public transport both in qualitative and quantitative terms has been recommended from all quarters. The present study assesses the existing 'quality of services' of midi buses operating in Patna, India. Accordingly, a Likert-type ordinal scale rating based face-to-face survey was conducted among midi bus users in Patna. Respondents were asked to rate the 20 attributes of midi bus services in the city, in terms of satisfaction based on their experiences while commuting. A total of 402 refined questionnaires were analyzed using TOPSIS method. The findings will help to understand the shortcomings of the existing public bus service and provide the responsible authorities and bus operators with suggestions that can enhance the 'quality of service' and attract more users to public bus service. Commuters were found satisfied with 'qualitative' attributes such as 'ticketing facility', 'seat comfort', 'condition of bus stops', 'condition of bus', etc. while dissatisfaction was found for 'bus information at the bus stop', 'frequency of bus service' and 'buses being on time'. This study justifies the need of improving 'qualitative' aspects of existing bus services. The findings of the study will provide the policy makers and bus operators in planning and implement the effective and sustainable public transport system in future for small and mid-sized cities of developing countries.